Clinical and molecular perspective of coronary artery calcification - Rohman, Mohammad Saifur; Firdaus, Dylan Hanny (Heart Science Journal, 2026)
Coronary artery calcification (CAC) has been known related to worse procedural outcome, repeated revascularization and increase major cardiovascular events. CAC is caused by chronic progressive inflammation result in deposition of calcium crystallization and phosphate in the form of hydroxyapatite which leads also to an ectopic mineralization formation. Current guidelines on treating CAC emphasized on multimodal approach using not only intravascular imaging but also debulking or lithotripsy device. Future studies are exploring the potential of molecular and genetic therapeutic targets to prevent disease progression.